Formulation development and evaluation of Luliconazole Topical Emulgel - K, Naga sai divya; T Malyadri; Ch.saibabu (International Journal of Indigenous Herbs and Drugs, 2021)
The purpose of the present study was to develop and optimize the emulgel system for Luliconazole using different types of gelling agents: HPMCK15M, Carbopol 940, and Xanthan Gum. The prepared emulgels were evaluated in terms of appearance, pH, spreadability, viscosity, drug content, and in-vitro drug release. In-vitro release study demonstrated diffusion-controlled release of Luliconazole from formulation up to 12 hours. The drug release profile exhibited zero-order kinetics. All the prepared emulgels showed acceptable physical properties concerning color, homogeneity, consistency, spreadability, and higher drug release. In the case of all evaluation parameters, carbopol based formulation showed better properties so, as a general conclusion, it was suggested that the Luliconazole emulgel formulation prepared with carbopol (F6) was the formula of choice.